Beyond Boundaries: Generative AI for Sustainable Academic Advancements - Bilal, Mushtaq (Actas del Congreso Internacional de Ingeniería de Sistemas, 2024)
Since its launch in November 2022, Open AI’s chatbot Generative Pre-trained Transformer, commonly known as ChatGPT, has become one of the most popular generative AI applications in the world (OpenIA, n. d.). Academics across the world are concerned about how ChatGPT is dramatically changing the pedagogical and research landscape. In this paper, I discuss some of the best practices for using ChatGPT for academic purposes.